Magnitude‐based discrimination of man‐made seismic events from naturally occurring earthquakes in Utah, USA. Issue 20 (18th October 2016) - Koper, Keith D.; Pechmann, James C.; Burlacu, Relu; Pankow, Kristine L.; Stein, Jared; Hale, J. Mark; Roberson, Paul; McCarter, Michael K.
Abstract: We investigate using the difference between local ( ML ) and coda/duration ( MC ) magnitude to discriminate man‐made seismic events from naturally occurring tectonic earthquakes in and around Utah. For 6846 well‐located earthquakes in the Utah region, we find that ML ‐MC is on average 0.44 magnitude units smaller for mining‐induced seismicity (MIS) than for tectonic seismicity (TS). Our interpretation of this observation is that MIS occurs within near‐surface low‐velocity layers that act as a waveguide and preferentially increase coda duration relative to peak amplitude, while the vast majority of TS occurs beneath the near‐surface waveguide. A second data set of 3723 confirmed or probable explosions in the Utah region also has significantly lower ML ‐MC values than TS, likely for the same reason as the MIS. These observations suggest that ML ‐MC is useful as a depth indicator and could discriminate small explosions and mining‐induced earthquakes from deeper, naturally occurring earthquakes at local‐to‐regional distances. Key Points: The difference between local ( ML ) and coda/duration ( MC ) magnitude separates mining‐induced seismicity from tectonic seismicity in Utah ML ‐MC acts as a depth discriminant with shallow events having more negative values ML ‐MC or similar metrics may also be useful for discriminating small explosions from tectonic earthquakes at local distances